2017
DOI: 10.7759/cureus.1533
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Rectal Toxicity in the Setting of Comorbid Crohn’s Disease Following Prostate Cancer Radiotherapy with a Hydrogel Rectal Spacer

Abstract: We present one of the first cases of a prostate cancer (PCa) patient with inflammatory bowel disease (IBD) treated with intensity-modulated radiotherapy (IMRT) and a hydrogel rectal spacer. A 73-year-old male with a past medical history significant for Crohn’s disease (CD) and the recent diagnosis of T1cN0M0 high-risk PCa was referred for definitive radiotherapy. Given the patient’s history of CD and the possible increased risk of gastrointestinal (GI) toxicity and disease exacerbation, prior to IMRT, a hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…37,38 Interestingly, there have been a few case reports of IBD patients achieving successful oncologic outcomes with minimal IBD flare-ups from prostate cancer radiotherapy after SpaceOAR placement. [39][40][41] These case reports suggest that the IBD patients with localized prostate cancer may be viable candidates for radiotherapy after SpaceOAR placement.…”
Section: Discussionmentioning
confidence: 82%
“…37,38 Interestingly, there have been a few case reports of IBD patients achieving successful oncologic outcomes with minimal IBD flare-ups from prostate cancer radiotherapy after SpaceOAR placement. [39][40][41] These case reports suggest that the IBD patients with localized prostate cancer may be viable candidates for radiotherapy after SpaceOAR placement.…”
Section: Discussionmentioning
confidence: 82%
“…Lehrich et al . reported on patients with prostate cancer and IBD, with 70% receiving a hydrogel rectal spacer at the time of EBRT with HDR-BT boost [ 7 , 23 ]. No patient experienced severe acute or late proctitis or diarrhea [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found an overall incidence of severe toxicity of 46% following abdominal and pelvic irradiation among patients with IBD, with 21% experiencing acute enteral toxicity that necessitated cessation of RT, and late toxicity requiring hospitalization or laparotomy due to complications of the small or large bowel [ 5 ]. Existing literature on the safety of EBRT in IBD patients with prostate cancer shows an association between EBRT and increased risk of gastrointestinal (GI) toxicity, though perhaps somewhat mitigated with the use of a hydrogel rectal spacer [ 6 , 7 ]. While advancements in radiation techniques have enabled more targeted delivery, EBRT still exposes the rectal-prostate interface and surrounding tissues in the lower pelvis to significant radiation.…”
Section: Purposementioning
confidence: 99%
“…Moreover, recent publications reported reduced risk of rectal toxicities in patients with IBD with placement of rectal spacers to displace the anterior rectal wall out of the field of radiation ( 102 - 105 ). In a case report, the use of hydrogel spacer in a patient with IBD and PCa treated with IMRT resulted in reduced rectal dose from 78.7 to 60.4 Gy, without and with the hydrogel spacer, respectively, resulting in Grade 1 GI toxicities of mild diarrhea.…”
Section: Ibd-associated Malignancies With Proximity To Bowelmentioning
confidence: 99%
“…In a case report, the use of hydrogel spacer in a patient with IBD and PCa treated with IMRT resulted in reduced rectal dose from 78.7 to 60.4 Gy, without and with the hydrogel spacer, respectively, resulting in Grade 1 GI toxicities of mild diarrhea. ( 102 ) One center treating 8 patients with IMRT and HDR brachytherapy boost with an injectable hydrogel spacer, with minimal acute toxicities and no late grade ≥2 gastrointestinal toxicities in the median 36 month follow up period ( 105 ). Similarly, the toxicity profile with the use of biodegradable rectal balloon implants inflated with saline is favorable and can be utilized in both the EBRT and brachytherapy setting ( 103 , 104 ).…”
Section: Ibd-associated Malignancies With Proximity To Bowelmentioning
confidence: 99%